Arte, cultura, ideologia: a mascarada da luta de classes - Pacheco, Tania (1991)
Culture has been playing a central role, in the mediation of class struggle in Brazil. The 'intelligentsia' acted as if it lingered over all classes (30s and 40s); tried to resume political leadership, ideologizing the nation (50s and 60s); was censored, tortured and exiled (70s). Since the beginning of the 80s, part of the intellectuals have joined political parties, in an attempt to work out a democratic project for the country, together with the proletarian classes. Nevertheless, pragmatism and conciliation seem to continue to be the best approach to analise the relationship between the majority of the 'intelligentsia' and the Brazilian government. For those, grants and subventions seem to be far more important than ethics and/or democracy.